Microenvironment-responsive metal-phenolic network release platform with ROS scavenging, anti-pyroptosis, and ECM regeneration for intervertebral disc degeneration - Hao Zhou; Jinpeng He; Renfeng Liu; Jun Cheng; Yuhao Yuan; Wanpu Mao; Jun Zhou; Honghui He; Qianqi Liu; Wei Tan; Cijun Shuai; Youwen Deng (Bioactive Materials, 2024)
Intervertebral disc degeneration (IVDD) can be caused by aging, injury, and genetic factors. The pathological changes associated with IVDD include the excessive accumulation of reactive oxygen species (ROS), cellular pyroptosis, and extracellular matrix (ECM) degradation. There are currently no approved specific molecular therapies for IVDD. In this study, we developed a multifunctional and microenvironment-responsive metal-phenolic network release platform, termed TMP@Alg-PBA/PVA, which could treat (IL-1β)-induced IVDD. The metal-phenolic network (TA-Mn-PVP, TMP) released from this platform targeted mitochondria to efficiently scavenge ROS and reduce ECM degradation. Pyroptosis was suppressed through the inhibition of the IL-17/ERK signaling pathway. These findings demonstrate the versatility of the platform. And in a rat model of IVDD, TMP@Alg-PBA/PVA exhibited excellent therapeutic effects by reducing the progression of the disease. TMP@Alg-PBA/PVA, therefore, presents clinical potential for the treatment of IVDD.